A case of hippocampal sclerosis diagnosed as cortical dysplasia due to preoperative brain MRI finding - Jun Seok Lee; Kyo Ryung Kim; Jeong Tae Kim; Min Jung Choi; Young Mock Lee; Heung Dong Kim; Joon Soo Lee; Dong Seok Kim; Tae Seong Kim (Korean Pediatric Society, 2010)
Hippocampal sclerosis (HS) is one of the most common features of intractable temporal lobe epilepsy. Generally it can be identified through brain magnetic resonance imaging (MRI) with high degree of sensitivity and specificity. Typical brain MRI findings of HS are hippocampal atrophy with hyperintense signal confined to the lesion. On the other hand cortical dysplasia exhibits blurring of the gray-white matter junction and abnormal white matter signal intensity. We present a case where preoperative brain MRI strongly suggested the presence of diffuse cortical dysplasia in the left temporal lobe but postoperative pathology revealed the temporal lesion to be unremarkable except for hippocampal sclerosis.